Analisis Penerapan dan Implementasi Prinsip-Prinsip Good Corporate Governance Syariah Di Perbankan Syariah - Muhammad Iqbal; Aldi Bastian; Iftasya Ainul Hafsah Sabran; Syofiah Harahap (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This article discusses the pivotal role of Good Corporate Governance (GCG) Sharia in governing the Islamic banking sector, emphasizing ethical principles and Sharia values. The research employs a comprehensive evaluation using secondary data collection methods, specifically library research and internet searches. Data were extracted from journals and articles focusing on GCG. The assessment reveals that Islamic banks have generally implemented GCG principles such as accountability, transparency, fairness, and compliance with Sharia law effectively. However, the study identifies areas for improvement, particularly in comprehensive application of Sharia principles and more effective risk management. Instances of personal involvement within Islamic banking institutions underscore the need for enhanced adherence to these principles to uphold ethics and sustainability. Therefore, this article underscores the significance of a profound understanding and effective implementation of GCG Sharia principles within the operational framework of Islamic banking in Indonesia.